2020
DOI: 10.1109/access.2020.2973919
|View full text |Cite
|
Sign up to set email alerts
|

Regularized Cubic B-Spline Collocation Method With Modified L-Curve Criterion for Impact Force Identification

Abstract: The time history of the impact force, especially for the peak force, is vital to monitor the performance of mechanical products over the lifetime. However, considering the limitation of sensing technology and inaccessibility of installing, it is always difficult or even impossible to measure the force directly in engineering practice. Therefore, a regularized cubic B-spline collocation (RCBSC) method combined with the modified L-curve criterion (RCBSC-ML) is presented to identify the impact force by easily mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Nonlinear parameters are not included in matrix boldBc, and the extended force vector contains only the excitation force. 11,12 Instead of NSI method, the LSI method 38 is applied to estimate new coefficient matrices to obtain a new transfer matrix. Then, the solving method is also TTLS combined with GCV criterion.…”
Section: Numerical and Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonlinear parameters are not included in matrix boldBc, and the extended force vector contains only the excitation force. 11,12 Instead of NSI method, the LSI method 38 is applied to estimate new coefficient matrices to obtain a new transfer matrix. Then, the solving method is also TTLS combined with GCV criterion.…”
Section: Numerical and Experimental Studiesmentioning
confidence: 99%
“…Wang et al 10 proposed a novel hybrid conjugate gradient algorithm to iteratively solve multisource force identification problems, and the identification results showed that the stability, robustness, and computational efficiency of the proposed iterative algorithm were superior to those of the traditional Landweber iteration regularization method. Since the profile of the impact force is similar to that of a cubic B-spline, Liu et al 11 presented a modified regularized cubic B-spline collocation method to identify the impact force. Because of the sparsity of the impact signal, Liu et al 12 introduced a fast iterative shrinkage-thresholding algorithm to solve a sparse regularization model developed from the dynamic response and impact force reconstruction equation, so as to synthetically estimate the above two physical quantities.…”
Section: Introductionmentioning
confidence: 99%
“…Impact energy is another characteristic parameter for characterizing impact damage of composite structures, the estimation of the impact energy is important for the evaluation of the health status of composite structures. At present, the estimation methods for impact energy can be classified into two main categories, namely (1) inverse the time history of the impact load by constructing a response model, and then estimate the impact energy magnitude 2631 ; (2) directly study the relationship between the magnitude of impact energy and signal characteristics, and then estimate the impact energy based on the signal characteristics. 32,33 In comparison, the second category of methods has the advantage of simplicity and efficiency by avoiding the need for extensive and complex modeling work.…”
Section: Introductionmentioning
confidence: 99%
“…The use of regularization methods, which mainly include direct regularization and indirect regularization, is the most effective way to improve these issues. The most used direct regularization methods are the Tikhonov regularization methods [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and the singular value decomposition (SVD) methods [ 28 , 29 , 30 ]. By comparing the generalized SVD method, the Tikhonov regularization method, and the truncated SVD method, Jacquelin [ 31 ] found that these methods have better robustness, and the convergence speeds are faster, but how to calculate the regularization parameters is still a difficult problem.…”
Section: Introductionmentioning
confidence: 99%